ANALISIS NILAI MANFAAT EKONOMI TANAMAN KEMIRI (Aleurites moluccana) DI DESA BUNGIN KECAMATAN BUNGIN KABUPATEN ENREKANG - Muthmainnah Muthmainnah; Irma Sribianti; Juliati Juliati (Jurnal Eboni, 2021)
This study aims to identify the value of economic benefits obtained from the Candlenut plant in Bungin Village, Bungin District, Enrekang Regency and to determine the economic benefit value of the candlenut plant in Bungin Village, Bungin District, Enrekang Regency. This research was conducted in Bungin Village, Bungin District, Enrekang Regency and this research will be carried out for approximately 3 months from September to November 2019. The research population is all people in Bungin Village, Bungin District, Enrekang Regency. The research sample was farmers who owned candlenut plants and the sampling was done by using purposive sampling technique. The people who earn from candlenut are 90 households using the Slovin formula with a tolerance of 15% error value. Based on the Slovin formula, the number of research samples is 30 people. Data analysis was carried out by recapitulating data from the respondents' results for the calculation of the economic benefit value of candlenut using a direct approach based on market prices. The results showed that the hazelnut plants obtained by the community were like candlenut fruit, candlenut shell, firewood and candlenut stands. The net income of the candlenut tree is Rp. 11.409.466 / year or 8,13% of candlenut, Rp. 54.107 / year or 0,04% of candlenut shell, Rp. 127.200 or 0.09% of firewood, and Rp. 128.700.000 stands of candlenut or 92,00%.